THE TEACHERS’ PERFORMANCE APPRAISAL AND DEVELOPMENT(TPAD) IMPLEMENTATION AND SCHOOL ORGANIZATIONAL CULTURE IN KIMILILI SUBCOUNTY, BUNGOMA COUNTY, KENYA - Dr. Masika Erastus K. (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of this study was to establish the relationship between TPAD implementation and school’s organizational culture among secondary school teachers in Kimilili sub county. The study population were all teachers who had interacted with TPAD. Thus 20 teachers were selected from 10 schools within Kimilili municipality to respond to the FGD schedule. Thus 2 respondents were selected from each school - 1 male and I female on equal gender basis and formed a FGD. Those who participated in FGD schedule were therefore 20. The sample comprised of teachers who had interacted with TPAD since 2017. Stratified sampling technique was used to sample 1 male and 1 female teacher. Simple random sampling technique was used to sample the 20 respondents on equal gender basis. Qualitative research design was used in the study which employed descriptive survey method. Data was collected and summarized into themes. It was then analyzed in verbatim form and translated into percentages. The results were presented in prose. The findings of the study revealed that successful TPAD implementation depended on the school’s organizational culture. Most aspects of firm school cultures were not present such as strong interpersonal relationships, internal appointments for responsibilities, quality of school meals, consenting of study leaves for teachers, participation in policy making, conflict resolution process, team spirit, welfare programs and teachers workload were all below average. The recommendations of the study therefore were: review of TPAD to address the challenges facing the wellbeing of teachers such as, fair internal appointment of teachers by school management, developing strong welfare organizations for teachers, motivation of teachers through rewards on exemplary performance, improvement on personal career development through consenting of study leaves and reduction of teachers’ workload through employment of more board of management(BOM) teachers. The recommendations of this study may inform the teachers’ employer on challenges facing teachers for better policies and improvements.